Finite Element Analysis of Heat Flow in Friction Welding - Kleiber, M.; Służalec, A. (Engineering Transactions, 1984)
In the Paper a finite element method is used for solving the nonlinear transient problem of the axisymmetric friction welding. The algorithm for solving the resulting system of nonlinear equations is shown. Numerical illustrations prove the effectiveness of the approach.